Applications of Multimodal Imaging in Central Serous Chorioretinopathy Evaluation - Mary Ho; Gabriel Li; Andrew Mak; Danny Ng; Lawrence Iu; Frank Lai (Journal of Ophthalmology)
Central serous chorioretinopathy (CSCR) is a macular disease characterized by serous retinal detachment commonly involving the macular region. CSCR has a wide spectrum of clinical presentations. Although a significant proportion of CSCR cases are self-limiting, patients can suffer from persistent or recurrent disease, sometimes complicated with choroidal neovascularization, resulting in permanent visual loss. Multimodal imaging, including fluorescein angiography, indocyanine green angiography, fundus autofluorescence, and optical coherence tomography, has advanced the diagnosis and classification of CSCR cases. Evolution of new imaging techniques including optical coherence tomography angiography, wide-field imaging, and en face reconstruction imaging has also contributed to better understandings of the pathophysiology of CSCR. This review article summarizes the features of multimodal imaging for CSCR and discusses the application of such features in evaluating the disease.